1992
DOI: 10.1080/00949659208811363
|View full text |Cite
|
Sign up to set email alerts
|

The effect of autocorrelation on the retrospectiveX-chart

Abstract: Quality control chart interpretation is usually based on the assumption that successive observations are independent over time. In this article we show the effect of autocorrelation on the retrospective Shewhart chart for individuals, often referred to as the X-chart, with the control limits based on moving ranges. It is shown that the presence of positive first lag autocorrelation results in an increased number of false alarms from the control chart. Negative first lag autocorrelation can result in unnecessar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(39 citation statements)
references
References 10 publications
0
38
0
1
Order By: Relevance
“…Alwan and Roberts (1988) proposed a general approach to monitor residuals of Univariate auto correlated time series where the systematic patterns are filtered out and the special changes are more exposed. Other studies include Montgomery and Friedman (1989), Harris and Ross (1991), Montgomery and Mastrangelo (1991), Maragah and Woodall (1992), Wardell, Moskowitz and Plante (1994), Lu and Reynolds (1999), West, Delana and Jarrett (2002) and West and Jarrett (2004), English and Sastri (1990), Pan and Jarrett (2004) suggested state space methodology for the control of auto correlated process. Further, additional technologies implemented by Testik (2005), Yang and Rahim (2005) and Yeh, Huang and Wu (2004) provide newer methods for enabling better MPC methods.…”
Section: Multivariate Quality Control (Mqc)mentioning
confidence: 99%
“…Alwan and Roberts (1988) proposed a general approach to monitor residuals of Univariate auto correlated time series where the systematic patterns are filtered out and the special changes are more exposed. Other studies include Montgomery and Friedman (1989), Harris and Ross (1991), Montgomery and Mastrangelo (1991), Maragah and Woodall (1992), Wardell, Moskowitz and Plante (1994), Lu and Reynolds (1999), West, Delana and Jarrett (2002) and West and Jarrett (2004), English and Sastri (1990), Pan and Jarrett (2004) suggested state space methodology for the control of auto correlated process. Further, additional technologies implemented by Testik (2005), Yang and Rahim (2005) and Yeh, Huang and Wu (2004) provide newer methods for enabling better MPC methods.…”
Section: Multivariate Quality Control (Mqc)mentioning
confidence: 99%
“…The study was restricted to a class of stationary ARMA models, AR (1), AR (2), and MA (1). Maragah et al (1992) also considered the capability of the Shewhart control chart but analyzed just the AR (1) and MA (1) models. These two studies came to the same conclusion -that even mild levels of autocorrelation can dramatically affect the Shewhart chart's ability to correctly separate assignable causes from random causes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Maragah and Woodall [3] provided results on the effect of autocorrelation on the performance of the Shewhart individuals control chart. Alwan and Roberts [4] found that more than 70% of the studied processes subject to change detection in quality control are autocorrelated.…”
Section: Introductionmentioning
confidence: 99%